Biosynthesis and Structural Properties of Sulfur Nanoparticles Using Proteus mirabilis Extract and its Effect on Pathogenic Bacteria (Journal of the College of Basic Education, 2024)
This research focuses on exploring the therapeutic potential of sulfur nanoparticles (sulfur NPs) synthesized from Proteus mirabilis (P. mirabilis) extract against Staphylococcus aureus )S. aureus), a pathogen implicated in skin infections. The study identified significant inhibitory effects of these nanoparticles on biofilm-producing and multidrug-resistant S. aureus isolates (A5, A8, A9, A11, and A29), with minimum inhibitory concentrations ranging from 16 to 32 µg/mL. While the study found no statistically significant differences in inhibition rates across various nanoparticle concentrations (p=0.842), there was a notable increase in anti-biofilm activity with higher concentrations (p<0.05). For instance, at 1024 µg/mL, the inhibition rate was approximately 93.1%, compared to 5.2% at 2 µg/mL (p=0.0001). These findings underscore the promising antimicrobial efficacy of sulfur NPs derived from P. mirabilis in combating drug-resistant S. aureus infections and biofilm formation commonly associated with dermatitis.